Health, Social, and Lifestyle Factors Related to Combined Alcohol and Sleep Problems: Investigating Risks of Chronic Pain, Welfare Benefits, Divorce, Smoking, and Low Physical Activity in Relation to Alcohol and Sleep Problems - Storvik, Mia Caroline (UiT Norges arktiske universitet, 2019)
The purpose of the study was to uncover whether there are increased risks associated to having combined alcohol and sleep problems in association to health, social, and lifestyle factors. This in comparison to having either alcohol and sleep problems, as opposed to having neither alcohol nor sleep problems. This study investigates potential risks in association to chronic pain, reception of welfare benefits, divorce, smoking, and physical activity. This was investigated by using data collected from the sixth Tromsø study, Tromsø 6. Results show that combined alcohol and sleep problems are associated to risks in chronic pain, welfare benefits, and smoking among men, and only smoking among women. For the same factors it seems that sleep is the decisive factor among women. This study has recognised some associations in combined problems and other factors, future studies are needed to decide the causality of the associations.